2009
DOI: 10.1177/0269216309106312
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of provision of palliative care to patients with cystic fibrosis

Abstract: Palliative care of patients with cystic fibrosis (CF) is often undertaken by CF teams rather than palliative care teams because of the specialist nature of the disease and the potential role of lung transplantation. We developed an integrated model of provision of palliative care whereby most care is delivered by the CF team using palliative guidelines and pathways, with additional support available from the specialist palliative care team when needed. We report our experience of the terminal care of 40 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…31 In a recently published descriptive analysis of 40 patients with cystic fibrosis, the age range (17-52 years) closely paralleled the age of our study sample. The end-of-life care in the patients with cystic fibrosis, who were dying from progressive endstage lung disease, 28 and 89% of whom died in hospital, was much less aggressive than in the patients with congenital heart disease in our cohort; only one patient with cystic fibrosis died in the intensive care unit on mechanical ventilation and only one patient had cardiopulmonary resuscitation attempted. We may speculate about reasons for differences in care in cystic fibrosis compared to congenital heart disease.…”
Section: Circumstances Of Death Of Admitted Patients With Congenital mentioning
confidence: 61%
See 1 more Smart Citation
“…31 In a recently published descriptive analysis of 40 patients with cystic fibrosis, the age range (17-52 years) closely paralleled the age of our study sample. The end-of-life care in the patients with cystic fibrosis, who were dying from progressive endstage lung disease, 28 and 89% of whom died in hospital, was much less aggressive than in the patients with congenital heart disease in our cohort; only one patient with cystic fibrosis died in the intensive care unit on mechanical ventilation and only one patient had cardiopulmonary resuscitation attempted. We may speculate about reasons for differences in care in cystic fibrosis compared to congenital heart disease.…”
Section: Circumstances Of Death Of Admitted Patients With Congenital mentioning
confidence: 61%
“…6 Similarly, there is a clinical impression that the quality of palliative care and the ability effectively to address end-of-life issues are enhanced when the transition to palliative and end-oflife care begins earlier in the course of the disease. 28 A recent study of adults with congenital heart disease found that most patients are in favor of starting these discussions earlier in the disease course. 29 This preference was independent of disease complexity and sociodemographic factors.…”
Section: Circumstances Of Death Of Admitted Patients With Congenital mentioning
confidence: 99%
“…Furthermore, adolescents with CF who had/were awaiting lung transplantation were excluded because of the exceptional status of this situation (e.g., very high level of symptoms, being terminally ill, intertwinement of end of life issues and hope of transplantation) (Bourke et al, 2009). One hundred and thirty adolescents, of whom 74 had CF and 56 had diabetes, met the inclusion criteria.…”
Section: Participantsmentioning
confidence: 99%
“…Discussions pertaining to longer-term outcomes and care strategies should begin from an early age, even prior to transfer to adult care. This is already practiced with patients with other pediatric-onset illnesses, such as cystic fi brosis, and research suggests that the quality of palliative care is enhanced when discussions begin earlier in the discourse of the disease [ 31 ]. As outlined earlier, adults with ConHD also favor earlier initiation of EOL discussions at a time when they are relatively healthy [ 24 ].…”
Section: Clinical Recommendationsmentioning
confidence: 99%